2017
DOI: 10.1371/journal.pone.0182330
|View full text |Cite
|
Sign up to set email alerts
|

Stroke survivors with severe mental illness: Are they at-risk for increased non-psychiatric hospitalizations?

Abstract: BackgroundThis study examined outcomes for two groups of stroke survivors treated in Veteran Health Administration (VHA) hospitals, those with a severe mental illness (SMI) and those without prior psychiatric diagnoses, to examine risk of non-psychiatric medical hospitalizations over five years after initial stroke.MethodsThis retrospective cohort study included 523 veterans who survived an initial stroke hospitalization in a VHA medical center during fiscal year 2003. The survivors were followed using adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…The physical effects of stroke are obvious, but the psychological effects are not always viable. A previous cohort study indicated that prestroke hospitalization was significantly related to severe mental illness (Lilly, Culpepper, Stuart, & Steinwachs, 2017). The current study clearly demonstrated low psychological scores among patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The physical effects of stroke are obvious, but the psychological effects are not always viable. A previous cohort study indicated that prestroke hospitalization was significantly related to severe mental illness (Lilly, Culpepper, Stuart, & Steinwachs, 2017). The current study clearly demonstrated low psychological scores among patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Liao et al51 found higher rates of postoperative complications and mortality rates in patients suffering from schizophrenia . Data unadjusted for sociodemographics and comorbidity indicate that mentally ill stroke survivors were more frequently hospitalized for nonpsychiatric reasons prior to and up to one year after their initial stroke 52. Patients with atrial fibrillation and schizophrenia or severe depression experienced increased rates of stroke and major bleeding compared with matched comparisons,53 and coagulation control is poorer in mentally ill patients 54.…”
Section: Discussionmentioning
confidence: 99%
“…This patient population is at increased risk for metabolic issues, such as obesity, which may have a modest effect on PPH risk. [26][27][28][29][30][31][32] The serotonergic agents used in mental health disorders may interfere with platelet aggregation and adhesion, increasing the risk for hemorrhage. 33,34 It is also possible that the mood disorder itself may impact serotonin transmission resulting in platelet dysfunction and subsequent bleeding.…”
Section: Discussionmentioning
confidence: 99%